Barley varieties registered in the Czech Republic in 2005. - Vratislav PSOTA (Kvasný průmysl, 2005)
Based on the results from tests for the registration procedure running in 2002-2004 the spring barley malting varieties Bojos, Class, Radegast, Sebastian and Timori were registered in the Czech Republic in 2005. Further, winter barley varieties Campill, Nives and Premuda were registered. Varieties Bojos and Radegast were mainly due to lower apparent final attenuation recommended as the varieties suitable for the production of Czech beer. The varieties Class and Sebastian with very good malting quality have high content of extract and higher fermentation. The variety Timori with low extract content was registered due to a low level of lipoxygenase.Based on the results from tests for the registration procedure running in 2002-2004 the spring barley malting varieties Bojos, Class, Radegast, Sebastian and Timori were registered in the Czech Republic in 2005. Further, winter barley varieties Campill, Nives and Premuda were registered. Varieties Bojos and Radegast were mainly due to lower apparent final attenuation recommended as the varieties suitable for the production of Czech beer. The varieties Class and Sebastian with very good malting quality have high content of extract and higher fermentation. The variety Timori with low extract content was registered due to a low level of lipoxygenase.